(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The aim of the research is to show the extent of the auditors’ commitment to the rule of fees and fees specified in the listed companies in the Iraqi market for securities and their impact on financial reporting. The researchers relied on the method of analyzing and discussing the reports of the auditors of a sample of listed companies in the Iraqi market for securities, The third axis was devoted to presenting the practical framework and testing the hypothesis of research. The fourth axis included the introduction of a set of conclusions, the most important of which is the poor awareness of The auditing firms, which audit the sample companies, investigate the importance of applying the fee and wages rule, which is reflected negatively in the financial reporting of the audited company, the weakness of the auditing program prepared by the audit offices, the sample of the research due to non-compliance with the rule of fees and wages and compliance with the rules of fees and wages by auditors , Provides confidence in the accounting information contained in the financial statements and therefore users of this information. As well as a set of recommendations that the two researchers deem necessary to be taken into account by the sample companies.